Pengaruh Media Tumbuh Kompos Terhadap Pertumbuhan Bibit Jabon Merah (Anthocephalus Macropyllus) - Chandra C. Mosooli; Marthen T. Lasut; Josephus I. Kalangi; Jos Singgano (COCOS, 2016)
ABSTRACTThe Research Anthocephalus growth macrophyllus (Roxb.) Havil) at various doses of compost have been carried out in the greenhouse of Faculty of Agriculture, forestry science courses Unsrat. The purpose of this study was to determine the effect of the growing medium compost on growth Anthocephalus macrophyllus. This study uses a randomized block design (RBD), with five treatments and five replications each test consists of 6 plants. Compost growing media treatment levels given are A control (without fertilizer) B (0.5 kg), C (1kg), D (1.5 kg), E (2kg). variable observed that the increase of plant height, stem diameter increase, in the number of leaves, root volume and dry weight of the plant. This study uses a randomized block design (RBD).The results showed that the growing medium compost significant effect on the growth of high and volume root crop seeds Anthocephalus macrophyllus. And the effect of high growth and volume Anthocephalus best root seedling compost macrophyllus is giving treatment that is as much as 1.5 kg at treatment D.Keyword : Compost, Seed Growth Anthocephalus macrophyllus